Improve Accounting Laws in the Public Sector to Prevent Fraud and Corruption in Vietnam - Hoang, Thanh Hanh, (Journal of Ecohumanism, 2024)
Corruption in the field of accounting and finance is new topic that is of interest to many researchers because of the increase in the number and scale of fraud, corruption and similar acts. This article analyzes the nature of fraud and corruption in the field of public accounting, thereby identifying structural factors that contribute to fraud and corruption in the application of accounting laws in the public sector. Finally, there are recommendations to improve the accounting laws in the public sector to prevent fraud and corruption in Vietnam. The article uses bibliometric analysis and systematic literature review (SLR) methods to analyze fraud and corruption in the field of public accounting. The main result of this study is to identify structural factors that lead to fraud and corruption in the field of public accounting